The Health Promotion Effectiveness On Mother Knowledge Of Stunting Prevention In Toddlers: Literature Review - Ghodiq Ufthoni; Bagoes Widjanark; Apoina Kartini; Tri Joko (Health Science Journal of Indonesia, 2022)
Background: The goal of public health promotion is to increase people's capacity for action through direct instruction from and for the general public, in order to enable them to take responsibility for their own well-being. It also aims to develop programs based on getting people involved in social activities that support healthy living. Stunting begins to occur when a child is two years old and occurs when the embryo is still inside the womb. Stunting is a condition when someone's normal level of badness is higher than the normal level of badness for someone else. Aim examine the effect of health promotion on mothers' knowledge about stunting prevention in toddlers. Method: Literature review is done by searching on direct science sites, Pubmed, and google scholar. They used the critical word The effect of health promotion on mothers' knowledge of stunting prevention in toddlers. References were selected based on the criteria of 1) journals related to stunting prevention, health promotion, and maternal knowledge, 2) 2017-2021 published years, and 3) fully accessible journals. Results: A total of 8362 journals were analyzed, but none of them fit the bill or had anything to do with how health education affects mothers' awareness of how to prevent stunting. The impact of health promotion on mothers' awareness of stunting prevention is then demonstrated from the 25 references found. In order to prevent stunting, health promotion involves a learning process that transforms bad behavior patterns into good ones. Conclusion: Health promotion is a learning process carried out to change unhealthy behavior patterns into healthy behavior so that stunting can occur. Keywords: Health promotion, knowledge, mothers, toddlers, stunting Abstrak Latar Belakang: Promosi kesehatan masyarakat adalah untuk meningkatkan kapasitas masyarakat untuk bertindak melalui instruksi langsung dari dan untuk masyarakat umum, agar memungkinkan mereka bertanggung jawab atas kesejahteraan mereka sendiri. Selain itu juga bertujuan untuk mengembangkan program yang berbasis pada keterlibatan masyarakat dalam kegiatan sosial yang mendukung hidup sehat. Stunting mulai terjadi saat anak berusia dua tahun dan terjadi saat embrio masih berada di dalam kandungan. Stunting adalah kondisi ketika tingkat keburukan normal seseorang lebih tinggi dari tingkat keburukan normal orang lain. Tujuan mengetahui pengaruh promosi kesehatan terhadap pengetahuan ibu tentang pencegahan stunting pada balita. Metode: Kajian pustaka dilakukan dengan mencari di situs ilmu langsung, Pubmed, dan google scholar. Menggunakan kata kunci Pengaruh promosi kesehatan terhadap pengetahuan ibu tentang pencegahan stunting pada balita. Referensi dipilih berdasarkan kriteria: 1) jurnal terkait pencegahan stunting, promosi kesehatan, dan pengetahuan ibu; 2) tahun terbit 2017-2021; 3) jurnal yang dapat diakses sepenuhnya. Hasil: Sebanyak 8362 jurnal dianalisis, namun tidak ada satupun yang sesuai atau berkaitan dengan bagaimana pendidikan kesehatan mempengaruhi kesadaran ibu tentang cara mencegah stunting. Dampak promosi kesehatan terhadap kesadaran ibu tentang pencegahan stunting kemudian ditunjukkan dari 25 referensi yang ditemukan. Kesimpulan: Untuk mencegah stunting, promosi kesehatan melibatkan proses pembelajaran yang mengubah pola perilaku buruk menjadi baik. Kata kunci: Promosi kesehatan, pengetahuan, ibu, balita, stunting